Prognostic and predictive value of EZH2 expression and the tumor immune microenvironment in Merkel cell carcinoma - Acikalin, Arbil; Bagir, Emine; Paydas, Semra (Polish Journal of Pathology, 2021)
Merkel cell carcinoma (MCC) is a rare and lethal type of skin cancer characterized by frequent recurrences and metastases. In view of the lack of a proven treatment option for MCC, we immunochemically evaluated the presence of Merkel cell polyomavirus (MCPyV), PD-1, PD-L1, CD8, and EZH2 on slides prepared from tumor tissues of 13 patients with MCC, and examined their association with disease progression and overall survival. PD-1 was expressed on tumor infiltrating lymphocytes (TILs) in 92.3% of the patients. None of the tumor cells expressed PD-L1. CD8 levels were higher in MCPyV-positive tumors. Interestingly, higher CD8 levels correlated with better overall survival (p = 0.025), while higher EZH2 expression correlated with metastasis/recurrence (z = –1.396, p = 0.089). However, low EZH2 expression was associated with poor overall survival (χ2 = 3.745, Cramer V = 0.537, p = 0.086). These findings suggest that EZH2 plays a significant role in MCC and may be a promising therapeutic target.